A Novel method of Starting Induction Motor - A Comparative Study - R L Chakrasali; V.R. Sheelavant; H.N. Nagaraja (International Journal of Power Electronics and Drive Systems (IJPEDS), 2011)
Polyphase induction motor, when started from rest with full voltage impressed, the starting current is 5 to 8 or more times the rated current. The large line current drawn by such a motor is objectionable because of the possible sharp drop in voltage of the supply circuit and undesired effects upon other connected loads/devices. Accordingly it is customary to start such motors at reduced voltage by using auto transformers, star delta starters etc. This paper deals with a new approach to start poly phase induction motors without using any primary voltage compensators thereby limiting the inrush of starting current. The rotor of the motor is driven at suitable speed in the specified direction of rotation by using crank driving mechanism. Then te rated voltage is applied to the motor. This is enunciated using a case study on a 3- phase, 5hp, NGEF make motor with oscillographic records obtained from the experimentation and is compared with the various starting techniques. Keywords: Induction motor, starter, inrush current, voltage dip, new approachDOI: http://dx.doi.org/10.11591/ijpeds.v1i1.70